Résistance et convenance dans Le Roi Pêcheur de Julien Gracq - Gerfaud, Jean-Pierre (Verbum – Analecta Neolatina, 2001)
In his essay, Mr Gerfaud focuses on the relationship between resistence (résistance) and conformity (convenance) as they are represented through the attitudes of the play’s protagonists. He also suggests a special interpretation of these two notions on the basis of the text.